2011
DOI: 10.1039/c0cp02742a
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of the ultrafast dissociative ionization dynamics of bromochloroalkanes

Abstract: We report on the coherent control of the ultrafast ionization and fragmentation dynamics of the bromochloroalkanes C(2)H(4)BrCl and C(3)H(6)BrCl using shaped femtosecond laser pulses. In closed-loop control experiments on bromochloropropane (C(3)H(6)BrCl) the fragment ion yields of CH(2)Cl(+), CH(2)Br(+), and C(3)H(3)(+) are optimized with respect to that of the parent cation C(3)H(6)BrCl(+). The fragment ion yields are recorded in additional experiments in order to reveal the energetics of cation fragmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…XUV transient absorption provides the unique capability of simultaneously observing the appearance of both charged and neutral atoms, as well as transient molecular configurations with femtosecond time resolution, from the perspective of well-defined reporter atoms. 24,25 Mass spectrometry and ion imaging techniques have shown that in strong-field ionized haloalkanes, a great multitude of effects can occur, including elimination of numerous charged fragments, 17,18,21 and in some cases new bond formation. 13,16,26 Recently, transient XUV absorption (TXA) experiments have been performed on two bromoalkanes, dibromomethane (CH 2 Br 2 ) 15 and vinyl bromide (C 2 H 3 Br), 19 following strong field excitation at intensities around 10 14 W cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…XUV transient absorption provides the unique capability of simultaneously observing the appearance of both charged and neutral atoms, as well as transient molecular configurations with femtosecond time resolution, from the perspective of well-defined reporter atoms. 24,25 Mass spectrometry and ion imaging techniques have shown that in strong-field ionized haloalkanes, a great multitude of effects can occur, including elimination of numerous charged fragments, 17,18,21 and in some cases new bond formation. 13,16,26 Recently, transient XUV absorption (TXA) experiments have been performed on two bromoalkanes, dibromomethane (CH 2 Br 2 ) 15 and vinyl bromide (C 2 H 3 Br), 19 following strong field excitation at intensities around 10 14 W cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…OCEs have been successfully performed for a wide range of goals, including the control of molecular vibrational [13][14][15][16][17][18][19][20] and electronic states [21][22][23][24][25][26][27][28][29], the generation and coherent manipulation of X-rays [30][31][32][33][34], the control of decoherence processes [35,36], the selective cleavage and formation of chemical bonds [37][38][39][40][41][42][43], the manipulation of energy flow in macromolecular complexes [44][45][46][47], and the control of photoisomerization reactions [48][49][50][51][52]. Optimal control theory (OCT) [7,9,[53][54][55][56] has provided insights into the coherent control of a variety of quantum phenomena, such as electron transfer …”
Section: Introductionmentioning
confidence: 99%
“…Successful optimal control experiments (OCEs) have included selective control of molecular vibrational [10][11][12][13][14][15][16][17] and electronic states [18][19][20][21][22][23][24][25][26][27], preservation of quantum coherence [28,29], control of photoisomerization reactions [30][31][32][33][34][35], selective manipulation of chemical bonds [36][37][38][39][40][41][42][43][44], high-harmonic generation and coherent manipulation of the resulting soft X-rays [45][46][47][48][49][50][51], and control of energy flow in biomolecular complexes [52][53][54][55]. Optimal control theory (OCT) [7,9,…”
Section: Introductionmentioning
confidence: 99%